Intravaginal GnRH Analogues in Rabbits: Fertirelin as the Most Effective Option for Ovulation Induction [Dataset] - Castillo, Juan José; Vicente, José Salvador; Marco-Jiménez, Francisco; Viudes-De-Castro, María P. (Instituto Valenciano de Investigaciones Agrarias (IVIA), 2025)
This dataset contains the data to compare the potency of three GnRH analogues (fertirelin, buserelin, and deslorelin) when administered intravaginally, and to determine the minimum effective concentration required to elicit an efficient ovulatory response. The file consists of two sheets, each with six columns. The first sheet includes data for a concentration of 3.5 µg of GnRH per insemination dose, while the second sheet contains data corresponding to a concentration of 1 µg per dose.